The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.21897/rmvz.2549
|View full text |Cite
|
Sign up to set email alerts
|

Perfil fermentativo, calidad nutricional y estabilidad aerobia de ensilajes mezclados de hierba elefante (Pennisetum purpureum Schum) y maní forrajero (Arachis pintoi)

Abstract: Objetivo. Determinar el perfil fermentativo, composición centesimal y estabilidad aerobia de ensilajes mezclados de hierba-elefante combinadas con niveles de maní forrajero. Materiales y métodos. Distintos niveles de maní forrajero (0,0, 20,0, 40,0, 60,0 y el 80,0% en la base de la materia fresca) se adicionaron a los ensilajes de hierba-elefante. Se adoptó el delineamento enteramente casualizado, con 5 tratamientos y 3 repeticiones, totalizando 15 silos experimentales que se abrieron tras 30 días de sellados.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…As the increase in temperature is related to the dry matter content of the silage [ 21 ], this effect demonstrates that the increase in silage DM promoted an increase in osmotic pressure, which reduced the activity of harmful microorganisms, improving its quality [ 15 ]. However, for the inclusion of gliricidia hay at levels above 20% in cactus pear silage, a reduction in temperature and DTS was observed, as also reported by Araújo et al [ 22 ] when Arachis pintoi was included in elephant grass silage. These authors found that the inclusion of up to 20% Arachis pintoi in silages caused an increase in the temperature and DTS of the silages and associated this result with the reduction in oxygen during fermentation, which tends to reduce the temperature of silages.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As the increase in temperature is related to the dry matter content of the silage [ 21 ], this effect demonstrates that the increase in silage DM promoted an increase in osmotic pressure, which reduced the activity of harmful microorganisms, improving its quality [ 15 ]. However, for the inclusion of gliricidia hay at levels above 20% in cactus pear silage, a reduction in temperature and DTS was observed, as also reported by Araújo et al [ 22 ] when Arachis pintoi was included in elephant grass silage. These authors found that the inclusion of up to 20% Arachis pintoi in silages caused an increase in the temperature and DTS of the silages and associated this result with the reduction in oxygen during fermentation, which tends to reduce the temperature of silages.…”
Section: Discussionsupporting
confidence: 83%
“…According to Marques et al [ 29 ], ether extract below 5% is beneficial so that feed intake by ruminants is not limited. Therefore, the combination of these roughages in the composition of mixed silages was inferred to have balanced the energy value of the silage [ 22 ]. The silages tested here can be used to feed ruminants as they allow for a higher intake by the animals and because they do not present limitations due to excess fiber, low protein concentration, or high energy concentration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%